The Evaluation of Tectonic Activity in Eshtehard Plain Basin with Interferometry - Farrin Nayebzadeh; Aghil Madadi; Ghasem Azizi (جغرافیا و پایداری محیط)
Tectonic and constructional movements have always played an important role in geomorphological changes. Identifying the nature of recent constructional movements has been of importance in understanding and interpreting landforms. In this research constructional movements in Eshtehard and Qazvin, located in the south and southwest of Tehran and southern slope of Alborz Mount, are investigated using Radar interferometry and geomorphological map of the basin. This technique is done using the images of Sentinel 1, which is located in band C radar range, with the average wave-length of 5/6 GHz. Geomorphological map of study area is provided in ArcMap GIS software, using Google-Earth images, DEM, Geological map, field visit, and sampling of landforms. Sentinel 1 Radar images are received from European Satellite site. Monitor changes are applied in SNAP software. According to the results of Radar Interferometry from 2015/10/3 to 2017/10/2, the whole study basin is tectonically rising. However, the rate of uplift in west and northwest of basin is greater than eastern and southern parts. Investigating geomorphological evidences such as consecutive alluvial fans, deviation of alluvial fans and remnants of lake terraces is totally in accordance with results from Radar interferometry indicating a high tectonic deviation speed in northwest of basin, that is around the city of Qazvin and Takestan, comparing with south and south-western of the basin. Extended Abstract 1-Introduction Neo-tectonic movements have created new surface landforms and controls their shapes and positions. So in the areas locating in tectonic activities’ range, there are forms which have been created under the influence of these activities. By investigating the forms mentioned above, it is possible to understand tectonic movements in most regions. However, using geo-morphological evidence for investigating tectonic movements is not useful in all regions, especially in the regions where erosion and other factors may reduce tectonic effects on geomorphology. In such regions using geo-morphological evidence is either inapplicable or very difficult and the results come with great doubts. A way used in computing displacement of events on earth’s surface, is Radar Interferometry including unique capabilities in terms of dimensions, cost, time and accuracy over other techniques. However, it should be noted that the use of this technique yields accurate results, especially in obtaining tectonic displacement rates, depending on the special features such as the base line, the polarization, the time interval between the two images, the time taken to take two images , passing sensors and so on. By following these tips, you can get great results from this technique. Therefore in this research we try to assess the rate of movements and its evidence in Qazvin and Eshtehard Plains in the past years. 2-Materials and Methods In this study, sentinel 1 images and geomorphology map are used to investigate tectonic dynamics. The date in which first image was taken is 2015/10/02, and the second day is 2017/10/03 with 731-day interval. The baseline rate is 47 meters than the original image that shows an acceptable rate in doing Radar Interferometry. For both images vv polarization has been used which is suitable for surface change measurement. In order to draw geomorphological map of the study area for recognizing geomorphological shapes, we used geological map of the region, Hill-shade, Satellite images, Google Earth images, Aerial Photos and Digital elevation Model (DEM). So, basic information about geomorphological landforms was obtained and an initial map of the geomorphology of the region was drawn. Then, in a field visit of the area, the landforms drawn on the map, were matched within the landforms on the earth and the items that were hard to detect on the map, were recognized. Finally, the supplementary map was detected. And in another field visit, the map bugs have been fixed. 3-Results and Discussion Consistency between images is more than 0.2 and in a range between 0.23 and 0.25. The pixel density above 0.6 is very small including 10% of all pixels. The phase difference values for pixels in Radar Interferometry, are between 3.14 to -3.14. Extensive patterns of fringes are related to tectonic movements in the region that are visible on plain margins and highlands. However, obtained maps of the phases are very complicated and in order to show them in real forms, they must be unwrapped. Opened phases indicate the general trend of phase changes in the region. But to investigate tectonic evidence reflected in landforms, the region’s geological map has also been used. The major sequences of alluvial fans are seen in the north basin and around Qazvin and Takisatan. Between these two cities sequence of three young alluvial fans and one old alluvial fan are noticeable. 4-Conclusion Having a look at this study, we conclude that the rate of tectonic uplift in northern margins of Qazvin and Eshtehard Plain Basin is more than that of southern parts. However, in the whole northern margins of the basin, this uplift is not the same; in northwest and west is more than northeast and east. In other words Qazvin and Eshtehard Plains around the cities of Qazvin and Takestan have the most uplift resulting in 3 new consecutive alluvial fans and an old one. In the north of Eshtehard plain there are low stretched hills that are 5 meters higher than surrounding areas. These parallel hills are stretched from south to the north with a west to east direction consisting of clay without layers that include a very calm and low slope deposition not so long ago. The erosion and direction of these clay deposits shows tectonic uplift in the west and north of the study area.